Chalice of God : A Systematic Theology in Outline - Nichols, Aidan (Book collections on Project MUSE., 2012)
"Over the course of a distinguished theological career, Aidan Nichols has produced an array of masterful contributions to the fields of systematic theology, ecclesiology, theological aesthetics, ecumenism, liturgy, and Scripture. Now, in Chalice of God, he attempts to synthesize a lifetime of research, teaching, and scholarly reflection in a book that is both rigorously academic and intensely personal. This is Nichols theological manifesto for the twenty-first century. Drawing together the insights of high scholasticism, the mid-twentieth-century ressourcement movement, a holistic reading of Scripture typical of the best patristic exegesis, and the liturgical tradition and iconography of both East and West, he presents a sound architecture for contemporary Catholic theology. Chalice of God promises to enrich and challenge those who engage in the enterprise of theology for years to come."--Publisher's description.